SMART WASTE BIN : IOT-BASED SMART TRASH BIN MONITORING SYSTEM - Dari, Ulan; Ikhwani, Muhammad; Saptari, Mochamad Ari (Universitas Muhammadiyah Sumatera Utara, Indonesia, 2025)
Unmonitored waste accumulation can cause environmental pollution and health risks, especially in campus environments with dense daily activities. This research developed the “Smart Waste Bin,” an IoT-based system that monitors trash bin conditions in real time. The system uses an ultrasonic sensor to measure the height of the waste and a NodeMCU ESP32 as the main controller. Data is displayed on an LCD and sent to a monitoring website and Telegram application for notifications. The system classifies waste levels into three statuses: Empty (1–11 cm, green), Nearly Full (12–20 cm, yellow), and Full (21–30 cm, red). It also includes an automatic lid operated by a servo motor. When the bin is full, the lid remains closed to prevent overflow and maintain cleanliness. Testing showed the prototype successfully detected bin status and sent notifications with 90–93% accuracy. However, the system heavily depends on stable internet connectivity. Overall, it effectively enhances waste monitoring using IoT integration